2002
DOI: 10.1101/gad.1020502
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for Foxd3 in maintaining pluripotent cells of the early mouse embryo

Abstract: Critical to our understanding of the developmental potential of stem cells and subsequent control of their differentiation in vitro and in vivo is a thorough understanding of the genes that control stem cell fate. Here, we report that Foxd3, a member of the forkhead family of transcriptional regulators, is required for maintenance of embryonic cells of the early mouse embryo. Foxd3−/− embryos die after implantation at approximately 6.5 days postcoitum with a loss of epiblast cells, expansion of proximal extrae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
231
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 303 publications
(238 citation statements)
references
References 36 publications
6
231
0
1
Order By: Relevance
“…All-stage WISH confirmed that the seven genes that we selected indeed showed the ICM-predominant expression. The expression patterns of Pou5f1 (Hanna et al, 2002;Pelton et al, 2002) and Nanog (Chambers et al, 2003;Mitsui et al, 2003) confirmed previously published results. Two new genes identified here were Mybl2 and Gtf2e2.…”
Section: All Stage Analysis Of Selected Genessupporting
confidence: 90%
See 1 more Smart Citation
“…All-stage WISH confirmed that the seven genes that we selected indeed showed the ICM-predominant expression. The expression patterns of Pou5f1 (Hanna et al, 2002;Pelton et al, 2002) and Nanog (Chambers et al, 2003;Mitsui et al, 2003) confirmed previously published results. Two new genes identified here were Mybl2 and Gtf2e2.…”
Section: All Stage Analysis Of Selected Genessupporting
confidence: 90%
“…While a pore size of 20 μm is necessary for achieving efficient drainage without special instruments, much smaller pores are preferable to maintain the best morphology of small samples. As a result, transwell with pore size 12 μm which are originally designed for cell culture were introduced into WISH (Hanna et al, 2002) to retain embryos. Although, solution changes were achieved by manually transferring the transwell from one well to another, it is difficult to have good buffer exchange through smaller pores without the assistance of a special device.…”
Section: Introductionmentioning
confidence: 99%
“…According to this theory, authors define tumor-progenitor genes as those that suffer epigenetic modification in stem cells thus promoting malignant transformation 137 . Examples of these tumor progenitor genes are, in addition to IGF2, the POU transcription factor OCT4 or the forkhead transcription factor FOXD3, whose inappropriate expression could augment proliferation and block differentiation in stem cells 145,146 . One additional example may be represented by two DNA repair genes, ataxia teleangiectasia mutated (ATM) and checkpoint kinase 2 (CHK2), frequently inactivated in mantle cell lymphoma.…”
Section: Tumor Progenitor Genes and Epigenetic Origin Of Cancermentioning
confidence: 99%
“…Foxd3 tm2.Lby is a null mutation of Foxd3 generated previously (Hanna et al, 2002) and is referred to as Foxd3 -throughout. Wnt1-Cre mice were a generous gift of Drs Andrew McMahon and David Rowitch (Harvard University, Cambridge, MA).…”
Section: Mouse Strainsmentioning
confidence: 99%
“…Foxd3 was first characterized by its expression in embryonic stem (ES) cells and multipotent cells of the NC (Labosky and Kaestner, 1998). Our previous work demonstrated that Foxd3 is required early in mouse embryogenesis; Foxd3 -/-embryos fail around the time of implantation, cells of the inner cell mass cannot be maintained in vitro, and ES cell and trophoblast stem cell lines cannot be established (Hanna et al, 2002;Tompers et al, 2005). In vivo, the pool of both embryonic and trophoblast progenitors is not maintained without Foxd3; embryonic progenitor cells die, while trophoblast progenitors give rise to an excess of trophoblast giant cells at the expense of the remaining trophoblast lineage.…”
Section: Introductionmentioning
confidence: 99%